The Determinants of Customer Loyalty for Telkomsel as a Telecommunication Provider in Pontianak - B12111003, MELYANTI THERESIA (Jurnal Manajemen Update, 2015)
Telecommunication has become inseparable element in human life. As the advancement of technology, the numbers of service provider has risen in order to support a better telecommunication. To retain its customers, certainly the telecommunication provider should have loyal customers. Three variables have been chosen to determine the customer loyalty, namely service quality, customer satisfaction, and switching cost. The data obtained from 100 Telkomsel users in Pontianak via questionnaire. The findings show that service quality did not show a relationship towards customer loyalty. Customer satisfaction and switching cost gave a positive and significant relationship on customer loyalty. Research indicates that Telkomsel must always maintain its customer satisfaction and switching cost, for instances, to offer interesting programs to create a high switching cost for its customers. Even though service quality is not significant, it doesnâ€™t mean it should be neglected. In terms of limitation, the next research should find more variables to represent service quality more. Besides, the next research could also put customer satisfaction as a mediating variable to see the indirect relationship between customer loyalty and service quality. Â  Keywords: service quality, customer satisfaction, switching cost, customer loyalty, telecommunication